(untitled) - Manivanh, Nouphone (Can Tho, 2012)
The objectives of the thesis were to study the use of ansiled taro foliage (leaves + stema) as the main source of protein for growing pigs fed rice bran as the basal diet
Keywords: Swine,Con lợn; Feeding and feeds,Thức ăn và thức ăn chăn nuôi